2021
DOI: 10.18502/ijps.v17i1.8050
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Maternal Personality and Internalizing/Externalizing Behaviors: Mediating Role of Maternal Alexithymia, Children’s Alexithymia and Emotional Regulation

Abstract: Objective: Although many studies have investigated the effect of maternal personality on internalizing and externalizing behaviors of a child, the role of both mother and child’s emotional mechanisms in these behaviors is little explored. The present study was focused on the relationship between the mother’s personality, and internalizing and externalizing behaviors of children with the mediating role of children’s alexithymia, mother’s alexithymia, and children’s emotion regulation (ER). Method: 162 mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Parental alexithymia was also significantly associated with greater parental perception of internalizing and depressive problems in their child (mothers: r = 0.261; p = 0.039; fathers: r = 0.340; p = 0.007). Similarly, Davodi-Boroujerd et al [ 96 ] showed that maternal alexithymia can act as relevant factor in the development of internalizing problems in children. Contingent stress imposed on parents by the pandemic may further have played a role in this regard, as highlighted by an increased maternal perception of internalizing symptoms in children after the COVID-19 outbreak compared to the pre-COVID-19 era [ 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…Parental alexithymia was also significantly associated with greater parental perception of internalizing and depressive problems in their child (mothers: r = 0.261; p = 0.039; fathers: r = 0.340; p = 0.007). Similarly, Davodi-Boroujerd et al [ 96 ] showed that maternal alexithymia can act as relevant factor in the development of internalizing problems in children. Contingent stress imposed on parents by the pandemic may further have played a role in this regard, as highlighted by an increased maternal perception of internalizing symptoms in children after the COVID-19 outbreak compared to the pre-COVID-19 era [ 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result reveals that mothers' inability of distinguish inner emotion has results in that children's tend to have more internalization behavioral problems such as withdrawn, somatic complaints and anxiety / depression but not increase externalization behavioral problems. [21,22] Another possibility was children with more internalization behavior problems would have a tendency to be alexithymic and decrease the probability of externalization. [23] There has difference of CBCL scores performance between boys and girls in general population.…”
Section: Discussionmentioning
confidence: 99%
“…The use of higher temperatures in the drying process can accelerate the drying rate because the rate of evaporation of water from the material to the air also increases with increasing temperature (Davodi-Boroujerd, Abasi, Arani, & Aslzaker, 2022). Then, the drying rate decreases with increasing time.…”
Section: Figure 6 Curve Of Drying Ratementioning
confidence: 99%